Staphylococcal Scalded Skin Syndrome in an Adult on Chemotherapy - Jonathan J. Lee; Hillary C. Tsibris; Arash Mostaghimi; Christine G. Lian (MDPI AG, 2014)
Staphylococcal scalded skin syndrome is a toxin-mediated, epidermolytic condition that uncommonly affects adults. A 51-year-old man receiving chemotherapy for leukemia presented with a large geographic erosion with superficial sloughing and multiple smaller lesions elsewhere. Biopsy revealed complete subcorneal splitting with multiple detached fragments of normal-appearing stratum corneum with fragments of attached acantholytic granular keratinocytes. Mild epidermal dysmaturation was also noted. Based on these findings, the patient was started on oral cephalexin, topical mupirocin, and topical clobetasol. His lesions improved significantly over the course of 1 week. © 2014 S. Karger AG, Basel